2008
DOI: 10.1038/nri2294
|View full text |Cite
|
Sign up to set email alerts
|

Resolving inflammation: dual anti-inflammatory and pro-resolution lipid mediators

Abstract: Active resolution of acute inflammation is a previously unrecognized interface between innate and adaptive immunity. Once thought to be a passive process, the resolution of inflammation is now shown to involve active biochemical programmes that enable inflamed tissues to return to homeostasis. This Review presents new cellular and molecular mechanisms for the resolution of inflammation, revealing key roles for eicosanoids, such as lipoxins, and recently discovered families of endogenous chemical mediators, ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
2,388
0
60

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 2,552 publications
(2,549 citation statements)
references
References 120 publications
36
2,388
0
60
Order By: Relevance
“…Potential beneficial effects of EPA on atherosclerotic plaque include anti‐inflammatory and antioxidant effects, decreased adhesion of monocytes to the endothelium, decreased macrophage and foam cell accumulation in fatty streaks, and increased thickness of the fibrous cap overlying lipid‐rich plaque28, 29, 30 (reviewed in Nelson et al) 31. EPA and DHA are also converted to specialized proresolving lipid mediators, with EPA and DHA being the respective precursors of the E‐series and D‐series resolvins 32. The resolvins have been shown to stimulate the resolution of acute inflammation by stopping further neutrophil recruitment to inflamed tissues and stimulating nonphlogistic infiltration of monocytes, which differentiate into resolution macrophages 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential beneficial effects of EPA on atherosclerotic plaque include anti‐inflammatory and antioxidant effects, decreased adhesion of monocytes to the endothelium, decreased macrophage and foam cell accumulation in fatty streaks, and increased thickness of the fibrous cap overlying lipid‐rich plaque28, 29, 30 (reviewed in Nelson et al) 31. EPA and DHA are also converted to specialized proresolving lipid mediators, with EPA and DHA being the respective precursors of the E‐series and D‐series resolvins 32. The resolvins have been shown to stimulate the resolution of acute inflammation by stopping further neutrophil recruitment to inflamed tissues and stimulating nonphlogistic infiltration of monocytes, which differentiate into resolution macrophages 33.…”
Section: Discussionmentioning
confidence: 99%
“…These resolution macrophages then phagocytize and clear apoptotic neutrophils and debris, a process termed efferocytosis, which is a key step in resolution and prevention of chronic inflammation 33, 34. Recent research has shown that omega‐3 fatty acids may hasten the resolution of inflammation when converted to resolvins 32, 33. Formation of fibrous tissue is an end stage of the chronic inflammatory process with the recruitment of collagen to form a scar.…”
Section: Discussionmentioning
confidence: 99%
“…The 14S-HDHA produced by platelets or lymphocytes was likely transported to macrophages and there converted to 14S,21R-diHDHA through the transcellular biosynthesis mechanism for lipid mediators. 43,44 Macrophages are the main leukocytes in wounds at days 2 to 3 after wounding, when the wounds are still in the inflammation phase. 2 They are activated to phagocytose apoptotic PMNs, debris, and bacteria, and then coordinate later events of healing, including re-epithelialization, granulation tissue formation, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the induction of inflammation leads to negative feedback pathways to resolve inflammation, via immune‐suppressive cytokines like IL‐10 or resolvins (Serhan et al ., 2008). These mediators enhance the clearance of dying neutrophils by macrophages, a process termed efferocytosis (Greenlee‐Wacker, 2016).…”
Section: Overview Of the Pathophysiology Of Inflammationmentioning
confidence: 99%